Breeding and fecundity of the sub-Antarctic crab Halicarcinus planatus (Crustacea: Hymenosomatidae) in the Deseado River estuary, Argentina - Ferrari, Lucrecia (2011)
Halicarcinus planatus is the only species of the genus occurring at the southern tip of South America, in sub-Antarctic, cold-temperate waters. Previously it has been shown that the population from the estuary of the Deseado River presents a spatial segregation by sex, a complete overlapping of sizes among adolescents and adult females. Females go through two reproductive seasons, separated by a resting period during late summer and early autumn, and 7 to 8 spawns are produced following a single mating. The aims of the present work were to evaluate the duration of the embryonic development until hatching during successive spawning, to determine the fecundity and to discuss the adaptive reproductive strategies of this population. Breeding occurs from nearly 2Â°C to above 16Â°C. The incubation period lasts nearly 100 days in winter and between 30 and 40 days in summer. The fecundity ranged from 210 to 2150 eggs, it differs between successive spawning and a positive relationship was found between fecundity and carapace width. This population has the highest fecundity compared to other populations, but also compared to other species of the genus. The high number of successive spawns is directly linked to the increase of seawater temperature by the end of spring and during summer. This way, this species would be very well adapted to live in the more temperate waters of Patagonian coasts.